Game-based teaching and gamification in ELE: cases and projects - Muriel, José Manuel Foncubierta; Santos, José María Rodríguez (Revista Letras Raras, 2023)
The present work deals with the game and the strategy resulting from the use of its elements, also known as gamification, as motors of the motivation of students of Spanish as a foreign language. Starting from the relevance of the game in the learning process from positions ranging from the anthropological to the neuroscientific, the ideas of the narrative component and the sensation of the game are addressed as prominent elements in this objective of involving students in learning tasks, providing specific practical cases on its application.